2007
DOI: 10.1063/1.2752158
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the shear-induced isotropic-to-lamellar transition of an amphiphilic model system: A nonequilibrium molecular dynamics simulation study

Abstract: The shear-induced isotropic-to-lamellar phase transition in the amphiphilic systems in the vicinity of the quiescent order-to-disorder transition point is investigated by the large-scale parallel nonequilibrium molecular dynamics simulations of simple amphiphilic model systems. There is a shear-induced upward shift of the ordering temperature. The initial isotropic phase orders into a lamellar phase perpendicular to the shear vorticity. The phase diagram as a function of temperature and shear rate is establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Afterwards, researchers theoretically predicted a phase transition of the lamellar [17][18][19][20], ring [21], hexagonal cylinders [22], diblock copolymer subjected to shear flow further. These predictions were proved by researchers using various numerical simulation methods, such as cell dynamics simulation (CDS) [23][24][25][26][27][28][29], nonequilibrium molecular dynamics simulation (NEMD) [29][30][31][32], dissipative particle dynamics method (DPD) [33][34][35], self-consistent field theory (SCFT) and lattice Boltzmann (LB) method [36], Brownian dynamics (BD) [37], mean-field approach (MFA) [38],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, researchers theoretically predicted a phase transition of the lamellar [17][18][19][20], ring [21], hexagonal cylinders [22], diblock copolymer subjected to shear flow further. These predictions were proved by researchers using various numerical simulation methods, such as cell dynamics simulation (CDS) [23][24][25][26][27][28][29], nonequilibrium molecular dynamics simulation (NEMD) [29][30][31][32], dissipative particle dynamics method (DPD) [33][34][35], self-consistent field theory (SCFT) and lattice Boltzmann (LB) method [36], Brownian dynamics (BD) [37], mean-field approach (MFA) [38],…”
Section: Introductionmentioning
confidence: 99%
“…As for the symmetrical block copolymer, Lisal and Brennan's simulation results indicated that the perpendicular lamellar phase persists for all shear rates investigated, whereas the parallel lamellar phase is only stable at low shear rates, and it becomes unstable at high shear rates [35]. In addition, Guo studied the amphiphilic model system: its kinetics of the shear-induced isotropic-to-lamellar transition [32], and the parallel-to-perpendicular orientation transition in the amphiphilic lamellar phase under shear flow [30,31]. Fraser et al investigated how shear flow affects the orientation of lamellar structures.…”
mentioning
confidence: 99%
“…Oriented lamellae have been obtained in simulations of a coarsegrained molecular model for lipids, [25][26][27] while defect dynamics has been investigated in simulations of a phasefield model of a smectic-A system. 28 Onion and intermediate states have large-scale structures of the order of micrometers, which are beyond typical length scales accessible to molecular dynamics (MD) simulations of coarse-grained surfactant molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The shear flow has been considered as an effective method for inducing long‐range order,3 structural transition,4,5 and the orientation of self‐assembled structures 6,7. The lamellar (LAM) block copolymers systems subjected to steady5–12 or oscillatory13–17 shear flow are most‐investigated. Koppi et al12 reported that near the order–disorder transition temperature ( T ODT ), shear induced a new state into poly‐(ethylenepropylene)–poly(ethylethylene) (PEP–PEE) lamellae, with their normals parallel to the vorticity axis (i.e., perpendicular alignment).…”
Section: Introductionmentioning
confidence: 99%
“…For steady‐shear flow, it was observed experimentally that the LAM structures adopted parallel alignment at low‐shear rates and perpendicular alignment at high‐shear rates, and that it was possible to use shear with varied rates to induce a transition between the parallel and perpendicular alignment 11. Besides the efforts in experiments, a lot of computational,5–9 and theoretical10 works have been carried out for elucidating the relation between the polymer phase behavior and shear rate for steady‐shear case. However, in experiments and manufacturing processes, the more common shearing mode is the oscillatory shear.…”
Section: Introductionmentioning
confidence: 99%